2014
DOI: 10.1210/en.2014-1385
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Insipidus: Celebrating a Century of Vasopressin Therapy

Abstract: Diabetes mellitus, widely known to the ancients for polyuria and glycosuria, budded off diabetes insipidus (DI) about 200 years ago, based on the glucose-free polyuria that characterized a subset of patients. In the late 19th century, clinicians identified the posterior pituitary as the site of pathology, and pharmacologists found multiple bioactivities there. Early in the 20th century, the amelioration of the polyuria with extracts of the posterior pituitary inaugurated a new era in therapy and advanced the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 176 publications
(114 reference statements)
1
37
0
2
Order By: Relevance
“…In neonate, CDI has been described as a complication of intrauterine and perinatal disease [3,4]. Some authors have suggested that possible causes of CDI may include asphyxia, severe infections, peri or intraventricular hemorrhage, and central nervous system abnormalities [1,2,4]. The state that is almost brain death caused by the severe perinatal asphyxia might develop in CDI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In neonate, CDI has been described as a complication of intrauterine and perinatal disease [3,4]. Some authors have suggested that possible causes of CDI may include asphyxia, severe infections, peri or intraventricular hemorrhage, and central nervous system abnormalities [1,2,4]. The state that is almost brain death caused by the severe perinatal asphyxia might develop in CDI.…”
Section: Discussionmentioning
confidence: 99%
“…CDI was diagnosed by the presence of hypernatremia (>150 mmol), high plasma osmolality (>300 mOsm), low urine osmolality (<300 mOsm/l), low plasma ADH levels, and recovery of serum sodium and urine osmolality after the administration of desmopressin [1][2][3]. In the present cases, hypernatremia, high plasma osmolality, low urine osmolality, and low plasma ADH levels (except case 1) with a good response to desmopressin (except case 3) easily led to the diagnosis of CDI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Возможность применения меньших доз препарата снижает риск развития таких тяжелых состояний, как гипонатриемия и судорожный синдром. Все это де-лает десмопрессин препаратом выбора для лечения центрального и гестационного несахарного диа-бета [25,42,55]. Первые препараты синтетического вазопрессина были созданы еще в 1954 г., в основном применялись интраназально и обладали более низкой эффективно-стью и продолжительностью действия, по сравнению с питрессином [10], но с учетом отсутствия необходи-мости в парентеральном введении зачастую являлись более предпочтительными [49].…”
Section: десмопрессин в лечении цндunclassified